(untitled) (Journal of Dhaka Medical College, 2010)
Context: This study was designed to observe the course of neutropenia that is onset of absolute neutropenia, depth of neutropenia and recovery pattern of neutropenia following induction chemotherapy and effect of granulocyte colony stimulating factor (G-CSF) on the course of neutropenia in adult acute myeloid leukaemia (AML) patients. Methods: A total of 34 newly diagnosed, adult, de novo AML patients opted to receive induction chemotherapy were enrolled for this study. All of them were given induction chemotherapy with cytarabine and daunorubicin as per 2+5 protocol. Four of them were dropped from this study; 2 due to early death and 2 due to resistant disease so were treated with early alternative chemotherapy regimen. So the ultimate sample of this study was 30 patients. Out of them 13 were given G-CSF following chemotherapy. Absolute Neutrophil count (ANC) of all patients were followed up until full recovery. Results: The difference in day of onset of absolute neutropenia (day 8 in G-CSF group vs. day 9 in no G-CSF group, P=.078) and number of day to reach nadir (day 11 in G-CSF treated group vs. day 12 in no G-CSF group, P=.688) was not significant between two group. The depth of neutropenia did not differ significantly as well (mean ANC 66/mm3 vs. 102/mm3, P=.184). However, recovery from absolute neutropenia was significantly (4 days) earlier in G-CSF treated patients (day 18 vs. day 22, P<.001). G-CSF treated patients also showed earlier attainment of ANC e"1,000/mm3 (day 20 vs. day 25, P<.001) and ANC e"1,500/mm3 (day 21 vs. day 27, P<.001). Duration of severe neutropenia was significantly shorter (9.6 days vs. 12.8 days P=.001) in G-CSF treated group. Key words: Acute myeloid leukaemia (AML); neutropenia; Granulocyte colony stimulating factor (G-CSF) DOI: 10.3329/jdmc.v18i2.6278 J Dhaka Med Coll. 2009; 18(2) : 155-160